Metabolic mechanism of colistin resistance and its reverting in Vibrio alginolyticus - Li, Lu; Su, Yu‐bin; Peng, Bo; Peng, Xuan‐xian; Li, Hui (Environmental microbiology, 2020)
Summary Colistin is a last‐line antibiotic against Gram‐negative multidrug‐resistant bacteria, but the increased resistance poses a huge challenge to this drug. However, the mechanisms underlying such resistance are largely unexplored. The present study first identified the mutations of two genes encoding AceF subunit of pyruvate dehydrogenase (PDH) and TetR family transcriptional regulator in colistin‐resistant Vibrio alginolyticus (VA‐RCT) through genome sequencing. Then, gas chromatography‐mass spectroscopy‐based metabolomics was adopted to investigate metabolic responses since PDH plays a role in central carbon metabolism. Colistin resistance was associated with the reduction of the central carbon metabolism and energy metabolism, featuring the alteration of the pyruvate cycle, a recently characterized energy‐producing cycle. Metabolites in the pyruvate cycle reprogramed colistin‐resistant metabolome to colistin‐sensitive metabolome, resulting in increased gene expression, enzyme activity or protein abundance of the cycle and sodium‐translocating nicotinamide adenine dinucleotide‐ubiquinone oxidoreductase. This reprogramming promoted the production of the proton motive force that enhances the binding between colistin and lipid A in lipopolysaccharide. Moreover, this metabolic approach was effective against VA‐RCT in vitro and in vivo as well as other clinical isolates. These findings reveal a previously unknown mechanism of colistin resistance and develop a metabolome‐reprogramming approach to promote colistin efficiency to combat with colistin‐resistant bacteria.